Near‐Enantiopure Trimerization of 9‐Ethynylphenanthrene on a Chiral Metal Surface. Issue 41 (13th August 2020) - Stolz, Samuel; Yakutovich, Aliaksandr V.; Prinz, Jan; Dienel, Thomas; Pignedoli, Carlo A.; Brune, Harald; Gröning, Oliver; Widmer, Roland
Abstract: Enantioselectivity in heterogeneous catalysis strongly depends on the chirality transfer between catalyst surface and all reactants, intermediates, and the product along the reaction pathway. Herein we report the first enantioselective on‐surface synthesis of molecular structures from an initial racemic mixture and without the need of enantiopure modifier molecules. The reaction consists of a trimerization via an unidentified bonding motif of prochiral 9‐ethynylphenanthrene (9‐EP) upon annealing to 500 K on the chiral Pd3 ‐terminated PdGa{111} surfaces into essentially enantiopure, homochiral 9‐EP propellers. The observed behavior strongly contrasts the reaction of 9‐EP on the chiral Pd1 ‐terminated PdGa{111} surfaces, where 9‐EP monomers that are in nearly enantiopure configuration, dimerize without enantiomeric excess. Our findings demonstrate strong chiral recognition and a significant ensemble effect in the PdGa system, hence highlighting the huge potential of chiral intermetallic compounds for enantioselective synthesis and underlining the importance to control the catalytically active sites at the atomic level. Abstract : Near‐enantiopure trimerization of an initial racemic mixture of prochiral molecules proceeds on an intrinsically chiral intermetallic PdGa{111} surface. This process demonstrates the immense potential of PdGa for asymmetric heterogeneous catalysis.